The effectiveness of project-based learning to teach writing in relation to students' creativity - Soffiany, Nur Kartika; Purbani, Widiastuti (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
This research was aimed to find out whether: (1) the use of project-based learning is more effective than direct instruction in the teaching of writing skills; (2) the students having high creativity have better writing skills than those having low creativity; (3) there is a correlation between teaching methods and creativity in teaching writing. This quasi-experimental research was conducted at SMP N 1 Yogyakarta in the academic year of 2016/ 2017. The sample was taken by using cluster random sampling. To collect the data, two instruments were employed. The data were analyzed by Multifactor Analysis of Variance ANOVA 2x2 and Tukey Test by IBM SPSS 22. The findings of this research can be stated as follow: (1) Project-Based Learning is more effective than direct instruction in teaching writing and it is indicated by the value of sig. (0.048); (2) the students who have high creativity have better writing achievement than the achievement of those who have low creativity and it is indicated by the value of sig. (0.000); (3) there is an interaction between teaching methods and students' creativity in teaching writing and it is indicated by the value of sig. (0.033). It means that the effect of methods and writing skills depends on the level of creativity of the students.